2011
DOI: 10.1186/1471-2164-12-235
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the symbiotic pangenome of the nitrogen-fixing bacterium Sinorhizobium meliloti

Abstract: BackgroundSinorhizobium meliloti is a model system for the studies of symbiotic nitrogen fixation. An extensive polymorphism at the genetic and phenotypic level is present in natural populations of this species, especially in relation with symbiotic promotion of plant growth. AK83 and BL225C are two nodule-isolated strains with diverse symbiotic phenotypes; BL225C is more efficient in promoting growth of the Medicago sativa plants than strain AK83. In order to investigate the genetic determinants of the phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 67 publications
4
89
0
2
Order By: Relevance
“…The genetic landscape adjacent to hrrP has been determined for only two plasmids: the pHR from strain B800 and an accessory plasmid (pSINME01) from S. meliloti strain AK83, which is noted for its ineffective nitrogen fixation (16). Despite 97.4% nucleotide sequence identity between these hrrP homologs, there is no synteny surrounding the hrrP coding region; even the promoter regions are highly divergent (Fig.…”
Section: Identification Of Host Range Restriction Peptidase As a Nitrmentioning
confidence: 99%
“…The genetic landscape adjacent to hrrP has been determined for only two plasmids: the pHR from strain B800 and an accessory plasmid (pSINME01) from S. meliloti strain AK83, which is noted for its ineffective nitrogen fixation (16). Despite 97.4% nucleotide sequence identity between these hrrP homologs, there is no synteny surrounding the hrrP coding region; even the promoter regions are highly divergent (Fig.…”
Section: Identification Of Host Range Restriction Peptidase As a Nitrmentioning
confidence: 99%
“…Notably, the NodD regulon, comprising luteolin-inducible and NodDdependent genes (Barnett et al 2004;Capela et al 2005), showed that the biosynthesis of NFs is one of the major pathways induced by the luteolin, but not the only one. Indeed, other additional genes are induced by the perception of plant flavonoid signals or show in their promoter region putative binding sites for NodD besides those related to NF biosynthesis (Batista and Hungria 2012;Galardini et al 2011;Lang et al 2008;Guerreiro et al 1997;Tolin et al 2013). Similarly to other plant flavonoids, luteolin was found to induce in E. meliloti, in addition to nod genes, the expression of genes encoding the EmrAB efflux pump, the GroES and GroEL chaperonins, as well as the SyrM transcriptional regulator and three hypothetical proteins (Capela et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies indicate that plasmid transfer or plasmid loss may increase nodulation or nitrogen fixation in Rhizobia strains (DeJonj et al, 1982, Pankhurst et al, 1986. Previous studies show that plasmid can be transferred from different genomic backgrounds that can extend nodulation hostrange (Galardini et al, 2011, Gonzalo et al, 2011. These observations taken together indicate that these isolates behave like parasitic organisms rather than bona-fide legume symbionts (Kundu and Dudeja, 2008, Oldroyd et al, 2011and Nadwani and Dudeja, 2013.…”
Section: Discussionmentioning
confidence: 99%